(untitled) (Pedagogy of Higher and Secondary Education, 2000)
This article presents the possibilities of personality orientative teaching in formation o f professional “I ” of specialist to come. The author substantiates it’s specific character and appropriateness. The calculation of these features in teaching process considerably improves the effectiveness of preparing of pedagogical personnel.